1997
DOI: 10.3109/03005364000000018
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Hearing-Impaired Word Recognition Scores for Monosyllabic Words in Quiet and Noise

Abstract: The effects of noise on word recognition scores were assessed with normal-hearing and hearing-impaired subjects. Fifty-one normal-hearing subjects were tested at 50 dB HL using signal-to-noise ratios (S/Ns) of 5, 10, and 15 dB. Thirty subjects with mild-to-moderate sensorineural hearing losses were tested in quiet and in noise at S/Ns of 10 dB and 15 dB. Monosyllabic words in a Multitalker Noise were selected for testing. Mean scores for the normal-hearing subjects were 45% at the 5 dB S/N, 74% at the 10 dB S/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Similar results have been reported in other studies (Dubno, Dirks, & Morgan, 1984, Frisina & Frisina, 1997Pichora-Fuller, Schneider, & Daneman, 1995). The effect of masking was even greater in the hearing-impaired, confirming previous studies (Beattie, Barr, & Roup, 1997;Dubno et al, 1984;Frisina & Frisina, 1997). One reason for this decreased performance in hearing-impaired patients is that sensorineural patients have proportionally less speech signal available for processing (Van Tasell, 1993).…”
Section: Behavioral Tests Of Speech Discriminationsupporting
confidence: 92%
“…Similar results have been reported in other studies (Dubno, Dirks, & Morgan, 1984, Frisina & Frisina, 1997Pichora-Fuller, Schneider, & Daneman, 1995). The effect of masking was even greater in the hearing-impaired, confirming previous studies (Beattie, Barr, & Roup, 1997;Dubno et al, 1984;Frisina & Frisina, 1997). One reason for this decreased performance in hearing-impaired patients is that sensorineural patients have proportionally less speech signal available for processing (Van Tasell, 1993).…”
Section: Behavioral Tests Of Speech Discriminationsupporting
confidence: 92%
“…EML listeners' performance agreed well with previous reports that used similar test stimuli and paradigms (e.g. Beattie et al, 1997). The superior performance of EML listeners over ESL listeners was expected given existing evidence (e.g.…”
Section: Listener Group Effectsupporting
confidence: 82%
“…Many professionals in the audiology community have suggested that audiologists should move away from the standard test protocol of testing word recognition in quiet and instead test speech recognition in noise. Problems recognizing speech in the presence of noise is the primary handicap of individuals with sensorineural hearing loss, and this type of testing better discriminates between individuals with hearing loss and those with normal hearing (e.g., Plomp and Duquesnoy [20], Pekkarinen et al [21], Beattie et al [22]). Further, a prior study we conducted and presented in this journal reported that this type of testing paradigm did show differences in performance between individuals with and without MS [23].…”
Section: Discussionmentioning
confidence: 99%